NEW HORIZONS IN HEALTH INEQUALITY: BRIDGING POLITICAL ECONOMY AND SOCIAL DETERMINANTS - Forsyth, Amelia Charlotte; Grafton, Henry William (International Research Journal Diagnostics, 2024)
The World Health Organization's definition of health as complete physical, mental, and social well-being, rather than mere absence of disease, underlines the significance of universal well-being. However, access to such well-being is far from uniform across the global population. Over the past three decades, these disparities have been illuminated by the framework of "social determinants of health" (SDH), as defined by the WHO. SDH encompasses the conditions in which individuals are born, raised, reside, labor, and age, serving as the fundamental drivers of these conditions. These factors range from economic measures like GDP per capita to community aspects such as educational institutions, public transportation, and even the prevalence of fast-food chains. While the availability and quality of medical care influence health outcomes, they have a more limited role in determining the initial susceptibility to illness. This abstract underscores the essential role of SDH in shaping health disparities globally, reflecting the complex interplay between social, economic, and environmental factors that impact individuals' well-being.